2017
DOI: 10.1186/s12879-017-2910-y
|View full text |Cite
|
Sign up to set email alerts
|

ORFeome-based identification of biomarkers for serodiagnosis of Mycobacterium tuberculosis latent infection

Abstract: BackgroundThe challenges posed by Mycobacterium tuberculosis infection require the gradual removal of the pool of latent tuberculosis infection (LTBI). The current cell-immune-based diagnostic tests used to identify LTBI individuals have several irreversible drawbacks. In the present study, we attempted to identify novel diagnostic antigens for LTBI.MethodsA high-throughput glutathione S-transferase (GST)-fusion technology was used to express over 409 TB proteins and sera from LTBI and healthy individuals was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…However, the immunogenicity of proteins even in this group varied significantly among patients with TB. A similar large variability in immunogenicity was described in a recent publication on TB serodiagnosis in 755 patients from several countries with a panel of 22 Mtb antigens preselected from the total proteome in the form of recombinant proteins [14], as well as in a work on the identification of biomarkers for the serodiagnosis of latent TB [22].…”
Section: Resultssupporting
confidence: 56%
“…However, the immunogenicity of proteins even in this group varied significantly among patients with TB. A similar large variability in immunogenicity was described in a recent publication on TB serodiagnosis in 755 patients from several countries with a panel of 22 Mtb antigens preselected from the total proteome in the form of recombinant proteins [14], as well as in a work on the identification of biomarkers for the serodiagnosis of latent TB [22].…”
Section: Resultssupporting
confidence: 56%
“…6). Despite the serodiagnosis of latent TB being very obscure, the work of Zhou et al (32), where serodiagnostic analysis was carried out using the sera of patients with confirmed latent TB at the proteome level, is of particular interest. Among 62 seropositive TB proteins reported by Zhou et al, 12 proteins out of 40 were found in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The shortened list of proteins was further compared with previously published datasets with annotated Mtb proteins with antigenic properties: i) a list of 181 proteins detected exclusively in the sera of TB-positive patients from a study on the dynamic antibody response to the proteome (31); ii) a list of 62 proteins resulting from serodiagnosis of latent Mtb infection (32); iii) a list of 22 proteins resulting from the analysis of TB-specific IgG antibody profiles, detectable on two different platforms (Luminex and MBio) (33).…”
Section: Methodsmentioning
confidence: 99%
“…However, none of any single antigen had enough high sensitivity. 15,16 In this study, we aimed to combine nine antigens (or segments) with un-conserved dominant B-cell epitopes to be a fusion polyprotein, which may improve the whole sensitivity and specificity compared with individual antigen and other combination forms. and E. coli were used to pre-adsorb the serum samples to block antibodies against bacteriaantigens and reduce non-specific reactions.In details,Bacteria were cultured at 100 mL volume overnight at 37℃ and then collected after centrifugation at 13,000 rpm at 4°C for 10 min.…”
Section: Aquatilis (V Aquatilis) Staphylococcus Aureus (S Aureus)mentioning
confidence: 99%